Efektivitas terapi inhibitor janus kinase pada vitiligo: tinjauan pustaka - Harry Gunawan; Flora Anisah Rakhmawati (DiscoverSys Inc., 2021)
Background: Vitiligo is an autoimmune disease that causes progressive skin melanocyte destruction, clinically seen as asymptomatic depigmentation macule and poliosis. CD8+ T cell is the primary effector of melanocyte destruction, and the activities of CD8+ T cell are driven by interferon-? (IFN-?). The current vitiligo treatment options are often not satisfied with many limitations and a high recurrence rate. Janus Kinase (JAK) inhibitor is one of the emerging vitiligo therapies which has a more specific target with a direct effect on CD8+ T cell cytotoxicity and IFN-?.Methods: In writing this article, the literature review method was used, and sources consist of relevant journals obtained through online search engines.Result: Several studies show that repigmentation in the facial area increases between 51-92%. Repigmentation occurs better in areas exposed to sunlight or a combination of phototherapy because repigmentation in vitiligo lesions requires suppression of the autoimmune process and melanocyte regeneration.Conclusion: Many studies showed the results of vitiligo therapy using JAK inhibitors were very promising and safe. The vitiligo therapy using JAK inhibitor showed higher efficacy on the facial area and combined with ultraviolet exposure. Latar belakang: Vitiligo merupakan penyakit autoimun yang menyebabkan destruksi melanosit secara progresif pada kulit, menimbulkan makula depigmentasi asimtomatik dan poliosis. Sel T CD8+ merupakan efektor primer yang menyebabkan kematian melanosit dan aktivitasnya ditingkatkan oleh interferon-? (IFN-?). Pilihan terapi vitiligo saat ini seringkali tidak memuaskan, memiliki keterbatasan, dan memiliki tingkat kekambuhan yang tinggi. Inhibitor Janus Kinase (JAK) merupakan salah satu terapi baru vitiligo yang memiliki target lebih spesifik dengan efek langsung terhadap sitotoksisitas sel T CD8+ dan IFN-?.Metode: Dalam penulisan artikel ini digunakan metode tinjauan pustaka dengan bersumber pada artikel relevan yang didapatkan melalui pencarian secara daring. Hasil: Beberapa studi menunjukkan adanya repigmentasi pada area wajah meningkat antara 51-92%. Repigmentasi terjadi lebih baik pada area terpapar sinar matahari atau kombinasi fototerapi disebabkan karena repigmentasi pada lesi vitiligo membutuhkan supresi dari proses autoimun dan regenerasi melanosit.Simpulan: Berbagai studi menunjukkan hasil terapi inhibitor JAK terhadap vitiligo sangat menjanjikan dan cukup aman. Terapi inhibitor JAK menunjukkan efektivitas lebih tinggi pada area wajah dan dengan kombinasi paparan ultraviolet.